I will find you [compact disc, unabridged] - Coben, Harlan, 1962- (Brilliance Audio, 2023)
David and Cheryl Burroughs were living the dream life when tragedy struck. Now, five years after that terrible night, Cheryl is remarried. And David is serving a life sentence in a maximum-security prison for the brutal murder of their son. Then Cheryl's sister, Rachel, arrives unexpectedly during visiting hours and drops a bombshell. She's come with a photograph that a friend took on vacation at a theme park with a boy in the background who has a familiar, distinctive birthmark, and even though David and Rachel realize it can't be, they both just know. It's David's son, Matthew, and he's still alive. David plans a harrowing escape from prison, determined to do what seems impossible, save his son, clear his own name, and discover the real story of what happened that devastating night.